2010
DOI: 10.1111/j.1365-2958.2010.07419.x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium mediates Escherichia coli enzyme IIANtr‐dependent regulation of sigma factor selectivity

Abstract: SummaryAn Escherichia coli mutant devoid of enzyme IIA Ntr (EIIA Ntr ) of the nitrogen PTS is extremely sensitive to leucine-containing peptides due to decreased expression of acetohydroxy acid synthase. This decreased expression is due to defective potassium homeostasis. We further elucidate here the mechanism for regulation of gene expression by the intracellular level of K + . The leucine hypersensitivity of a ptsN (encoding EIIA Ntr ) mutant was suppressed by deleting rpoS, encoding the stationary phase s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 67 publications
0
54
0
1
Order By: Relevance
“…Transcriptome analysis revealed that the expression of many genes is affected by a ptsN deletion, with the most dramatic effect being upregulation of the S regulon (132). It was concluded that K ϩ regulates the selectivity of RNA polymerase toward 70 or S such that, with high K ϩ levels, RNA polymerase preferentially binds S (132).…”
Section: The Regulatory Pts (Pts Ntr )mentioning
confidence: 99%
“…Transcriptome analysis revealed that the expression of many genes is affected by a ptsN deletion, with the most dramatic effect being upregulation of the S regulon (132). It was concluded that K ϩ regulates the selectivity of RNA polymerase toward 70 or S such that, with high K ϩ levels, RNA polymerase preferentially binds S (132).…”
Section: The Regulatory Pts (Pts Ntr )mentioning
confidence: 99%
“…However, in the presence of certain carbohydrates the EIIA Ntr protein (encoded by the ptsN gene) is dephosphorylated (Pflüger-Grau & Görke, 2010), and this dephosphorylated product binds to and inhibits the potassium transporter TrkA, which decreases the concentration of intracellular potassium and thus reduces potassium-dependent gene expression (Lee et al, 2007(Lee et al, , 2010. Thus, the presence of glucose might inhibit the enzyme activity of TnaA simply by reducing potassium stores.…”
Section: Inhibition Of Tnaa Is Not Caused By Known Mechanisms Associamentioning
confidence: 99%
“…Indeed, a ptsN mutant accumulates high concentrations of K ϩ inside the cells. K ϩ differentially affects the binding of 70 and S to apo RNA polymerase and thus influences factor selectivity (122). In contrast to EIIA Ntr , phosphorylated EIIA Ntr does not interact with TrkA.…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%